Where the locals go more than 300 places around the world to eat, play, shop, celebrate, and relax - National Geographic Traveler (Firm).; National Geographic Society (U.S.). (Washington, D.C. National Geographic Society, 2014)
For many, the joy of travel is often an authentic, immersive experience of the local culture. Here, National Geographic's insider tips offer a unique look at the places and activities around the world that captivate the residents--from regional festivals, undiscovered local restaurants, and lesser-known art galleries, to quiet places to sit and watch another world stroll by. A bonus chapter features in-depth experiences in the top 15 greatest cities. This book goes beyond Internet basics to ensure rewarding and memorable travel for those who crave a deeper understanding of a country and its people. When in Rome, they say, do as the Romans do. Discover the soul of a place through a chance encounter, a kind word, or an unparalleled tip from a local. In Where the Locals Go, you'll find hundreds of authentic, beautifully photographed travel experiences, complemented with nuggets of entertaining and insightful text informed by locals. Now, you, too, can join the locals in Venice on their evening passeggiata; mingle with the crowds at sunset on Juhu Beach in Mumbai; sample some of France's best cheeses in the Alpine town of Annecy; and walk the ancient peak-to-peak pilgrimage on Japan's Kunisaki Peninsula. This book will inspire you to make your next trip a truly authentic travel experience.
North America -- South America & the Caribbean -- Europe -- Great cities -- Africa & the Middle East -- Asia & the Pacific.
Includes index.
Keywords: Travel -- Guidebooks